The influence of Mg2+ coordination on 13C and 15N chemical shifts in CKI1RD protein domain from experiment and molecular dynamics/density functional theory calculations - Vícha, Jan; Babinský, Martin; Demo, Gabriel; Otrusinová, Olga; Jansen, Séverine; Pekárová, Blanka; Žídek, Lukáš; Munzarová, Markéta L (Proteins, 2016)
Sequence dependence of (13) C and (15) N chemical shifts in the receiver domain of CKI1 protein from Arabidopsis thaliana, CKI1RD , and its complexed form, CKI1RD •Mg(2+), was studied by means of MD/DFT calculations. MD simulations of a 20-ns production run length were performed. Nine explicitly hydrated structures of increasing complexity were explored, up to a 40-amino-acid structure. The size of the model necessary depended on the type of nucleus, the type of amino acid and its sequence neighbors, other spatially close amino acids, and the orientation of amino acid NH groups and their surface/interior position. Using models covering a 10 and a 15 Å environment of Mg(2+), a semi-quantitative agreement has been obtained between experiment and theory for the V67-I73 sequence. The influence of Mg(2+) binding was described better by the 15 Å as compared to the 10 Å model. Thirteen chemical shifts were analyzed in terms of the effect of Mg(2+) insertion and geometry preparation. The effect of geometry was significant and opposite in sign to the effect of Mg(2+) binding. The strongest individual effects were found for (15) N of D70, S74, and V68, where the electrostatics dominated; for (13) Cβ of D69 and (15) N of K76, where the influences were equal, and for (13) Cα of F72 and (13) Cβ of K76, where the geometry adjustment dominated. A partial correlation between dominant geometry influence and torsion angle shifts upon the coordination has been observed.
Keywords: proteinkinasy; hořčík; Arabidopsis thaliana; izotopy dusíku; nukleární magnetická rezonance biomolekulární; density functional theory; Mg2+ coordination; NMR chemical shift; CKI1 histidine kinase; Arabidopsis Proteins; Molecular Dynamics Simulation; Nitrogen Isotopes; proteiny huseníčku; Protein Domains; molecular dynamics; Protein Kinases; 15N; izotopy uhlíku; Carbon Isotopes; Magnesium; simulace molekulární dynamiky; proteinové domény; Nuclear Magnetic Resonance, Biomolecular; 13C